THE FACTORS THAT INFLUENCE PATIENT SATISFACTION AT DANOWUDU HEALTH CENTRE IN BITUNG CITY - Tumatar, Carenina A.; Kindangen, Paulus; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2019)
Abstract: The health center is a functional organization that organizes comprehensive, integrated, equitable, acceptable and affordable health efforts, with active participation of the community and uses the results of the development of appropriate science and technology. Health Center as health service providers must be able to meet patient expectations and are required to always maintain trust and maintain patient satisfaction. The purpose of this study was to find out and analyze the factors that influence patient satisfaction at Danowudu Health Center in Bitung City. The type of this research is quantitative research with causal analysis by using multiple linear regression methods. Data collection using a questionnaire. The population of this study were patients who often visited the Danowudu Health Center, with a sample size of 100 respondents. Finding of this research shows that employee performance, service quality and facilities simultaneously influence customer satisfaction. The results also show that employee performance, service quality and facilities partially influence customer satisfaction. This research offered several recommendations for health center in carefully managing the patient satisfaction. For this reason, the Danowudu Health Center must maintain good employee performance, maintain service quality and maintain existing facilities in order to attract new patients and maintain existing patients.Â Keywords: customer satisfaction, employee performance, service quality, facilities, health center